Turbulent drag reduction by wavy wall - Ghebali,S; Chernyshenko,S; Leschziner,M (2017)
Fully-developed turbulent flow in channels with oblique wavy walls is analysed, from a drag-reduction perspective, by means of Direct Numerical Simulations (DNS). The wavy geometry is chosen to emulate the shear strain produced by a Spatial Stokes Layer (SSL) generated by oscillatory wall motion. As the cost of performing a parametric optimisation is prohibitive, an alternate solution is presented, based on a linear model of a perturbed plane-channel flow, using a turbulent viscosity. Flow properties and levels of drag reduction or increase are reported for various configurations.